"Ukraine on Fire" by Oleksandr Dovzhenko in the context of philosophical ideas about the evolution of culture and civilization of the 20th century (Oswald Spengler, Mykola Khvylovyi, Francis Fukuyama, Samuel Huntington) - Тримбач, Сергій (Видавничо-поліграфічний центр “Київський університет”, 2024)
The article deals with the creative legacy of film director Oleksandr Dovzhenko during World War II, primarily the film story "Ukraine on Fire", and its modern context. Despite the realities that minimized the presence of Ukrainians in the historical field, the artist presents Ukrainianness as an authoritative subject of the military confrontation of peoples. The song-romantic image of the people overcoming all the terrible trials of wartime is recreated. he story was subjected to devastating criticism by Joseph Stalin and banned as a nationalist work, one that revises the very foundations of the Soviet state system. An analysis of Dovzhenko's texts from the war years suggests that the artist perceived the terrible cataclysms that brought the very existence of the Ukrainian people to the brink of catastrophe as a systemic sin of the Bolshevik regime led by Stalin. A regime that opposed itself to Europe not only ideologically, but also as an autonomous socio-cultural organism. This corresponded to the concept of the German philosopher Oswald Spengler, which was based on the idea that there is no holistic world culture, it is made up of autonomous cultural organisms. Each of which has its own genetic program of development, from birth to death. Western European ("Faustian") culture, according to Spengler, is in a stage of total aging, degradation, transition to civilization (ossification of cultural organisms) and needs "donor assistance" from younger cultures. Among the latter is the youngest, which was born in the territories of the former Russian Empire, including Ukraine. Mykola Khvylovyi built his own idea of the German philosopher's concept, based on the Asian Renaissance, Ukraine as the vanguard of the newest cultural and historical type, an organic compound, cosmic in its naturalness. It is through it that Europe will renew itself, refreshing its strength, its energy. Simultaneously, Ukraine itself will borrow something from Europe from its acquisitions, the process here is mutual. Dovzhenko's work is also in the context of similar ideas, from the film "Earth", the film story "Ukraine on Fire" to "The Enchanted Desna". According to Samuel Huntington's popular concept of the "clash of civilizations", the borders that divide humanity in the modern world are determined not by ideology, not by economics, but by culture. It is not nation-states that are in conflict, but nations and groups belonging to different civilizations, and their clash is the dominant factor in world politics. Despite the idea, once formed by Francis Fukuyama, that the history of global conflicts effectively ended at the end of the 20th century. The current Russian-Ukrainian war in the above-mentioned context is a war for the affirmation of civilizational meanings and attitudes. From the Ukrainian side, it is a struggle for a return to Western civilization. A struggle that was defined and discussed by Ukrainian intellectuals, among them Dovzhenko, back in the 1920s and 1930s.

У статті йдеться про творчу спадщину кінорежисера Олександра Довженка часів Другої світової війни, переДусім кіноповість "Україна в огні", та її сучасний контекст. Попри реалії, які мінімізували присутність українців в історичному полі, митець поДає українство як повноважного суб'єкта військового протистояння нароДів, як автономну культурну систему. Це віДповіДало концепції німецького філософа ОсвальДа Шпенглера, в основі якої лежало уявлення про те, що не існує цілісної світової культури, її склаДають автономні культурні організми. Микола Хвильовий вибуДував своє власне уявлення щоДо концепції німецького філософа, в основі якого про Азійський ренесанс, Україна як авангарД найновішого культурно-історичного типу. За концепцією "зіткнення цивілізацій" Семюеля Гентінгтона, таке зіткнення цивілізацій стало панівним фактором світової політики. Попри уявлення, свого часу сформованого Френсісом Фукуямою про фактичне завершення історії глобальних конфліктів.
"Україна в огні" Олександра Довженка в контексті філософських уявлень щодо еволюції культури і цивілізації ХХ ст. (Освальд Шпенглер, Микола Хвильовий, Френсіс Фукуяма, Самуель Гантінгтон)
Keywords: culture; civilization; Renaissance; Europe; Ukraine; conflict; clash; культура; цивілізація; ренесанс; Європа; Україна; конфлікт; зіткнення